(3JSgjd GdegeGJ aj TQM GdCegGJs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s ((3eMeO Hf eMeO Hf eMeO GdegdH s)
(3ChdgG (B:s
(3bGd GdTjN Gdabjg HGHf GdMGLH GdejGg CbSGe GdeWdb WghQ hgh GdKGfi Ydi NdbJg s
(3BNQgG (B:s
(3egeGJ GdKGdK ai Med GdRhLI abjd Hhba GdLejY hhUGjGg MJi JVY ced GdcJGH hGdMeO ddg Ydi Pdc cKjQkG Edi jhe GdOjf s
(3GdfSNI HgG MhGTs
(3HBNQg fbhd eNJdaIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs